Characterization of the Buoyant Jet above a Catalytic Combustor Using Wavelength Modulation Spectroscopy. Issue 6 (2nd June 2020) - Hayden, Torrey R. S.; Wimer, Nicholas T.; Lapointe, Caelan; Christopher, Jason D.; Nigam, Siddharth P.; Upadhye, Aniruddha; Strobel, Mark; Hamlington, Peter E.; Rieker, Gregory B.
ABSTRACT: Combustion-based processing of polymer films and other materials often requires temporal and spatial uniformity of the combustor. We characterize the temperature and H2 O mole fraction of the buoyant jet above a rectangular iron-chromium catalytic combustor using diode-laser wavelength modulation spectroscopy (WMS). The sensor is first validated in a tube furnace under known conditions. It is then used to characterize the temporal and spatial variation of the flow exiting the combustor. The H2 O mole fraction measurements incorporate a new pathlength correction approach that uses computational fluid dynamics to account for the changes in jet width. We observe 3% temporal variation of temperature over 60 s and 7% spatial variation along the length of the burner. Vertical profiles indicate that additional combustion is likely occurring above the catalytic surface under certain operating conditions. This type of characterization can be used for optimizing the combustor for a variety of catalytic combustion applications.